Functional and radiological outcomes of posteriorly stablised total knee joint arthroplasty - Mohammed , Raaid Abed (International Journal of Psychosocial Rehabilitation, 2020)
BACKGROUND: To prevent posterior subluxation of the tibia and to improve both range of motion and stair climbing ability, the TCP was modified to the Insall Burstein Posterior Stabilized Prosthesis (IB I) in 1978. The posterior-stabilized condylar knee was specifically designed to improve stair-climbing ability and range of motion and to prevent posterior tibial subluxation.These goals were certainly achieved with the new“cruciate- substituting” design. PATIENTS&METHODS: We prospectively studied 30 patients who are randomly selected underwent PS/TKA.The mean age of the patients at operation was 63 years ( 4975 years) and mean follow-up was 12 months range (3-18 months).The diagnosis of causative disease was OA (24 knees, 3 of them posttraumatic) and the rest 6 knees were RA. All knees were unstable (10 knees in multidirections, 16 in AP. and 24 in mediolat. dierections) and malaligned (23 varus, 7 valgus). The clinical and radiographic results were assessed using the scoring system described by Insall et al.(1989) and the parameters described by the Knee Society Score (Ewald 1989). Preoperatively, anteroposterior weight- bearing radiographs were taken in order to determine lower extremity alignment. Postoperative radiological assessment was performed from weight-bearing anteroposterior and supine lateral radiographs taken at every visit on flow up. RESULTS: At latest visit, 9 knees (30%) had an excelent result, 18 knees (60%) had a good result and 3 knees (10%) had a fair result. The improvement in the mean Knee Society Score was from 31(OA:49/RA:33.5) points preoperatively (range 25-55 points) to 89 (OA:89/RA:86) points postoperatively (range 77-95). The mean ROM (flexion) preoperatively was 68.5o [OA:70o/RA:45o] (range 45o-100o) was improved to 106o [OA:110o/RA:90o] (range 90o-120o). All were stable in AP direction and in 4 patients (13.3%) a slight instability was noted in the lateral direction. The ideal position for femoral component within (6-10o) valgus was obtained in 24 knees (80%). The femoral prosthesis was within (0-5o) valgus in 6 knees (20%). Ninety three percent (28) of the tibial component were within 2o of varus or valgus, 6.6% (2 knees) was in greater than 2o of varus. Knee function score was improved from a mean 27.5 (OA:26/RA:25) points preoperatively to 58 (OA:59/RA:55) points postoperatively and the patient able to walk more than 5 blocks(1/2km) and less than 10 blocks(1km). CONCLUSIONS: Posterior stabilized total knee arthroplasty would allow increase range of motion, increase joint stability and improved gait. Because OA and RA are the predominant knee diseases, one could see that both OA and RA patients respond well to treatment with PS/TKA with the same end results. These clinical results on short-term basis are encouraging and justify continuation of its use. We strongly recommend the use of a cemented, posterior stabilized total knee arthroplasty for primary total knee arthroplasty.